2018
DOI: 10.1186/s12902-018-0242-6
|View full text |Cite
|
Sign up to set email alerts
|

The association of Val109Asp polymorphic marker of intelectin 1 gene with abdominal obesity in Kyrgyz population

Abstract: Significant increase in the frequency of Val109Val genotype of ITLN1 gene in AO patients may be indicative of some potential role of ITLN1 gene in molding genetic predisposition to AO in the Kyrgyz. This requires further elaboration in the future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 17 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Isakova et al investigating Kyrgyz population reported that the Val/Val genotype was significantly more prevalent in the patients with abdominal obesity than in the healthy controls (OR = 3.12). However, the allelic variants of Omentin Val 109 Asp polymorphism did not correlate with abdominal obesity [34].…”
Section: Discussionmentioning
confidence: 99%
“…Isakova et al investigating Kyrgyz population reported that the Val/Val genotype was significantly more prevalent in the patients with abdominal obesity than in the healthy controls (OR = 3.12). However, the allelic variants of Omentin Val 109 Asp polymorphism did not correlate with abdominal obesity [34].…”
Section: Discussionmentioning
confidence: 99%
“…Omentin is encoded in humans by the ITLN1 gene and located within the 1q22-q23 chromosomal region. The common rs2274907 polymorphism of the omentin gene exists a polymorphic locus in position 326 of the fourth exon, where adenine is replaced with thymine (326 GAC→GTC, rs2274907), which entails the replacement of aspartic acid with valine in position 109 of ITLN1 (Val109Asp) (Isakova et al 2018). The previous studies found an association of this omentin gene rs2274907 with daily energy intake (Splichal et al 2015), cardiovascular diseases (Jamshidi et al 2017), and type 2 diabetes (Rathwa et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is caused by energy imbalance: when the energy gained from calories is greater than the energy expended from physical activity; the body stores the extra calories as fat (Alharbi et al, 2017). There is an increased prevalence of being overweight and obesity globally (Isakova et al, 2018). Per the World Health Organization (WHO), the global prevalence of obesity in adults is 13%, and it is 18% in children aged 5–19 years (Aguayo-Armendáriz et al, 2018).…”
Section: Introductionmentioning
confidence: 99%